The Lecturer’s Strategies in Overcoming the Obstacles in Teaching Listening - Nasir, Vebiyanti (International Journal of Education, Information Technology, and Others, 2024)
The aims of the research were to know (1) the lecturer’s obstacles in teaching listening, (2) the lecturer’s strategies in overcoming the obstacles, and (3) the sudents’ motivation and attitude in learning listening. The data was conducted by interview in semi-structured interview with the lecturer and structured interviewed with the students, and doing the observation toward the lecturer’s obtacles and the strategies, and the students’ motivation and attitude. The result of the research found that the lecturer’s obstacles in teaching listening were in four factors. The first was students factors: the students’ lack in vocabularies and grammar, and the students’ low motivation in learning listening. The second was speakers factor: the speakers’ accent especially the native speakers’ accent in conversation make the students difficult and can not catched the uttarances by the speakers because they speak too fast. The third was teaching methods factors: the lecturer used inappropriate material for the college students. The fourth was classroom fasilities: unreadiness of listening material books, unreadiness of language laboratory and unreadiness of listening module for the students. Furthermore, the strategies used by the lecturer in overcoming the obstacles consisted of predicting strategy to overcome the students’ low motivation. Monitoring, evaluating and clarifying strategy to solve the obstacle with students’ lack in grammar and vocabularies. Responding and monitoring strategy to overcome the problem about the speakers. The lecturer used material based on students’ level to solve the teaching method problem about in appropriate listening materials for college students. The lecturer used material from another resources to taught the students, the using of language laboratory from other school for teaching listening and gave materials for the students to independent study to overcome the unreadiness of listening module. In addition, the result of the research also found that the students’ motivation in learning listening were in moderate level and the students’ attitude toward learning listening were in high positive attitude.